Detection of Extensive Cross-Neutralization between Pandemic and Seasonal A/H1N1 Influenza Viruses Using a Pseudotype Neutralization Assay - Labrosse, Béatrice (Public Library of Science, 2010)
BACKGROUND: Cross-immunity between seasonal and pandemic A/H1N1 influenza viruses remains uncertain. In particular, the extent that previous infection or vaccination by seasonal A/H1N1 viruses can elicit protective immunity against pandemic A/H1N1 is unclear. METHODOLOGY/PRINCIPAL FINDINGS: Neutralizing titers against seasonal A/H1N1 (A/Brisbane/59/2007) and against pandemic A/H1N1 (A/California/04/2009) were measured using an HIV-1-based pseudovirus neutralization assay. Using this highly sensitive assay, we found that a large fraction of subjects who had never been exposed to pandemic A/H1N1 express high levels of pandemic A/H1N1 neutralizing titers. A significant correlation was seen between neutralization of pandemic A/H1N1 and neutralization of a standard seasonal A/H1N1 strain. Significantly higher pandemic A/H1N1 neutralizing titers were measured in subjects who had received vaccination against seasonal influenza in 2008–2009. Higher pandemic neutralizing titers were also measured in subjects over 60 years of age. CONCLUSIONS/SIGNIFICANCE: Our findings reveal that the extent of protective cross-immunity between seasonal and pandemic A/H1N1 influenza viruses may be more important than previously estimated. This cross-immunity could provide a possible explanation of the relatively mild profile of the recent influenza pandemic.